Effect of CuCl2 treatment on RF magnetron-sputtered CdSe thin films for potential photovoltaic usage. (1st June 2022) - Ibrahim, Mohamad; Chelvanathan, P.; Mottakin, M.; Muhammad, Ghulam; Miraz, Mahdi H.; Akhtaruzzaman, Md.; Shahiduzzaman, Md.; Sobayel, K.; Kamal, N.
Abstract : CuCl2 solutions of various molarities were used to treat CdSe thin films produced by RF magnetron sputtering. In-depth investigation on the impacts of this treatment on CdSe thin films were studied. The structural investigation revealed that all as-grown films exhibited the hexagonal phase peak at the (101) plane. The crystalline and grain sizes increased with CuCl2 treatment, reaching 114 nm for 0.1 M CuCl2 -treated CdSe thin film. A granule-like morphology was seen on the treated films. Opto-electric study revealed that CuCl2 treatment improved CdSe film properties and tailored structural restrictions. The 0.30 M CuCl2 treatment was shown to be an important process parameter for the CdSe thin films, indicating its potential as a photovoltaic material.